Desenvolvimento de néctar à base de mamão (Carica papaya L.) adicionado de inulina e oligofrutose - Braga, Héberly Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The demand for food and functional ingredients has increased, in particular by the prebiotics. The incorporation of inulin and oligofructose in fruit drinks, as nectars, is an alternative to increase nutritional value to products. Among fruits, the papaya is an excellent choice because of its easy cultivation, high productivity, low cost, high nutritional value and, particularly, the shortage of this fruit nectar in the Brazilian market. The study aimed to develop papaya nectars with different concentrations of sugar, oligofructose and inulin. Nectars were prepared with 6, 8, 10 and 12% sugar (without fructan) and the ideal sweetness of sugar was determined. From the formulation considered ideal sweetness, the mixtures modeling methodology was applied to assess the effects of the interaction between sugar, oligofructose and inulin on the acceptance sensory and chemical characteristics of papaya nectars (dependent variables). The sensory acceptance regarding to appearance, aroma, viscosity, flavor, sweetness and overall evaluation and purchase intent was evaluated, using a nine point hedonic scale and categorical scale of five points, respectively. The results of sensory acceptance were also assessed by cluster analysis and principal component analysis to construct internal preference maps. The formulations were characterized regarding to soluble solids and total, titratable acidity, total sugars, ash and pH. The best formulation for overall assessment was monitored for two weeks for pH, titratable acidity, mesophilic, psychrotrophic, yeasts and molds, total and fecal coliforms. The formulation with 12% sugar was considered ideal for sweetness by 36% of the panelists. The interaction between the ingredients sugar, oligofructose and inulin influenced the acceptance for the taste and the sweetness of the nectar, and the formulation with 6% sugar and 6% inulin was the most acceptable for these attributes. The preference for attributes of this ...

A demanda por alimentos e ingredientes funcionais tem aumentado, em particular pelos prebióticos. A incorporação de inulina e oligofrutose às bebidas de frutas, como o néctar, torna-se uma alternativa para agregar valor nutritivo aos produtos. Dentre as frutas, o mamão representa uma excelente opção devido ao fácil cultivo, alta produtividade, baixo custo, alto valor nutritivo e particularmente à escassez do néctar dessa fruta no mercado brasileiro. O trabalho objetivou desenvolver néctares de mamão com diferentes concentrações de açúcar, oligofrutose e inulina. Foram elaborados néctares, sem frutanos, com 6, 8, 10 e 12% de açúcar e determinado o ideal de doçura em açúcar. A partir da formulação considerada ideal em doçura, foi aplicada a metodologia de modelagem de misturas para avaliar os efeitos da interação entre açúcar, oligofrutose e inulina na aceitação sensorial e características químicas dos néctares de mamão (variáveis dependentes). As formulações foram avaliadas sensorialmente quanto à aceitação (aparência, aroma, viscosidade, sabor, doçura e avaliação global) e intenção de compra, empregando-se escala hedônica de nove pontos e escala categórica de cinco pontos, respectivamente. Os resultados da aceitação sensorial também foram avaliados por meio da análise de Cluster e Análise de Componentes Principais para construção dos mapas de preferência internos. As formulações foram caracterizadas quimicamente quanto ao teor sólidos solúveis e totais, acidez total titulável, açúcares totais, cinzas e pH. A formulação mais aceita para avaliação global foi monitorada durante quinze dias quanto ao pH, acidez total titulável, bactérias mesófilas, psicrotróficas, bolores e leveduras, coliformes totais e termotolerantes. A formulação com 12% de açúcar foi considerada como ideal em doçura por 36% dos julgadores. A interação entre os ingredientes açúcar, oligofrutose e ...
Keywords: Tecnologia de alimentos; Mamão - Indústria; Néctar; Inulina; Frutanos; Frutas - Industria; Prebióticos; Alimentos - Avaliação sensorial; Papaw